Increased total plasma TGF-β1 levels and deregulated IgA - IgM axis in chronic obstructive pulmonary disease - Minic, Rajna; Đukić, Olivera; Kosanović, Dejana; Žujović, Dejan; Ilić, Aleksandra; Panić, Marko; Đorđević, Brižita (Journal of Medical Biochemistry, 2025)
Background: Chronic obstructive pulmonary disease (COPD) is displayed as the obstruction of the small airways and includes “flare-ups”, sudden and significant worsening of symptoms, sometimes caused by infections. Methods: COPD (n=38) and acute bronchitis (AB, n=35) patients were grouped based on age and examined at two time points: during flare-ups/infections and at day 30. We measured various biomarkers, including total plasma TGF-β1 levels, total IgA, total IgM, and Pseudomonas aeruginosa specific IgA levels. Results: Increased TGF-β1 levels were detected in COPD patients, with no significant change observed at day 30. A significant lowering of total plasma IgA level was observed in COPD patients on day 30. No significant difference in specific P. aeruginosa IgA levels were observed between the two patient groups, or over time. Interestingly, a correlation between total IgM and IgA levels was absent in COPD patients. While positive correlation between age and IgA level existed in acute bronchitis patients, this correlation was negative in COPD patients. A significant correlation was observed between total IgA and P. aeruginosa specific IgA in acute bronchitis patients. On the other hand, COPD patients showed no correlation at t=0 but a correlation was seen between total IgA and P. aeruginosa specific IgA1 at t=30, implying that flare-up resolution is accompanied with consolidation, a corresponding reinforcement or stabilization, of P. aeruginosa specific IgA levels in COPD patients. Conclusion: Here we report on deregulated IgA - IgM axis in COPD, and call for thorough, larger scale studies of the humoral immune system in this pathology.